2021
DOI: 10.1021/acs.biochem.1c00305
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of a Multimodular Hyperthermostable Xylanase-Glucuronoyl Esterase from Caldicellulosiruptor kristjansonii

Abstract: The hyperthermophilic bacterium Caldicellulosiruptor kristjansonii encodes an unusual enzyme, CkXyn10C-GE15A, which incorporates two catalytic domains, a xylanase and a glucuronoyl esterase, and five carbohydrate-binding modules (CBMs) from families 9 and 22. The xylanase and glucuronoyl esterase catalytic domains were recently biochemically characterized, as was the ability of the individual CBMs to bind insoluble polysaccharides. Here, we further probed the abilities of the different CBMs from CkXyn10C-GE15A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…No binding data are currently available for these however, and it is an open question what part(s) of the cell wall these CBM2 modules target. One studied bacterial GE that is coupled to several CBMs and that has been thoroughly investigated is Ck GE15A [ 33 , 39 ]. The full-length Ck Xyn10C-GE15A enzyme does not comprise only the GE, but consists of two N-terminal CBM22 modules, linked to a glycoside hydrolase family 10 (GH10) xylanase, three additional CBM9 modules before the GE domain, which is followed by cadherin and surface-layer homology domains thought to anchor the large enzyme to the outer Gram-positive cell wall.…”
Section: Ge Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“…No binding data are currently available for these however, and it is an open question what part(s) of the cell wall these CBM2 modules target. One studied bacterial GE that is coupled to several CBMs and that has been thoroughly investigated is Ck GE15A [ 33 , 39 ]. The full-length Ck Xyn10C-GE15A enzyme does not comprise only the GE, but consists of two N-terminal CBM22 modules, linked to a glycoside hydrolase family 10 (GH10) xylanase, three additional CBM9 modules before the GE domain, which is followed by cadherin and surface-layer homology domains thought to anchor the large enzyme to the outer Gram-positive cell wall.…”
Section: Ge Diversitymentioning
confidence: 99%
“…The full-length Ck Xyn10C-GE15A enzyme does not comprise only the GE, but consists of two N-terminal CBM22 modules, linked to a glycoside hydrolase family 10 (GH10) xylanase, three additional CBM9 modules before the GE domain, which is followed by cadherin and surface-layer homology domains thought to anchor the large enzyme to the outer Gram-positive cell wall. Interestingly, the CBMs display various binding properties, and collectively enable the protein to bind virtually all major plant cell wall glycans [ 33 , 39 ]. Likely, also other CBM-appended GEs benefit from CBMs to help guide them to their complex LCC target substrate, or close proximity thereof.…”
Section: Ge Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…CesA, a bimodular acetyl xylan esterase-glucuronoyl esterase, studied by Aurilia, et al [ 101 ] as component of the cellulosome from Ruminococcus flavefaciens , revealed a C terminal domain whose GE function was subsequently demonstrated by Biely et al [ 102 ] after its expression in E. coli . A multiple domain glucuronoyl esterase (CkXyn10C-GE15A), containing a module with xylanase activity and others with carbohydrate binding function, was studied from the hyperthermophilic bacterium Caldicellulosiruptor kristjansonii [ 103 ]. CkXyn10C-GE15 is the most thermostable GE studied so far, with an optimal temperature around 72 °C.…”
Section: New Challenges For Biocatalysts and The Circular Economymentioning
confidence: 99%